Relación entre clima laboral y motivación laboral en analistas de crédito de coopac grupo Inversión Sudamericano, Arequipa, 2021 - Corahua Supho, Estefani Yuri (2022)
Objective:To determine if there is a relationship between work environment and work motivation in credit analysts working in COOPAC Grupo Inversión Sudamericano -Arequipa, during the period 2021.Method:The present study belongs to the quantitative, non-experimental, cross-sectional and relational approach. The information was obtained from a primary source, from a sample of 80 credit analysts, who responded to two survey-type instruments with characterization variables of 50 items for the work environment variable and 19 items for the work motivation variable. The data obtained were processed with the SPSS-26 statistical program. The descriptive results were presented with frequencies, percentages and measures of central tendency, and the hypothesis test was performed with Pearson's r parametric correlation statistic.Results:Credit analysts have a favorable work environment (77.5%) and medium-high work motivation (72.5%). When correlating work climate and work motivation, p: 0.001 and r: 0.378 were obtained, which means that there is a significant, positive, low level correlation at 99% confidence and 1% error. From this it can be concluded that the better the work climate, the higher the work motivation and the worse the work climate, the lower the work motivation. Therefore, work climate is a factor associated with work motivation. Similar results were obtained when correlating the dimensions of work climate with work motivation.Key words:work climate, work motivation, organizational climate.